Moral management in competitive markets. Issue 3 (25th September 2018) - Martin, Steve
Abstract: The intrinsic motivation of a firm's management for engaging in prosocial behavior is an important determinant of a firm's social conduct. I provide the first model in which firms run by morally motivated managers engage in corporate social responsibility (CSR) in a competitive setting. Moral management crowds out a competitor's strategic CSR, increasing profitability and leading shareholders to strategically delegate moral managers, although necessary for socially optimal CSR is that shareholders be morally motivated as well. Shareholders appoint managers that engage in a socially excessive amount of CSR, counter to existing literature, whenever product‐market competition is sufficiently intense.